2016
DOI: 10.1051/matecconf/20167801097
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties and Potential Applications of Bamboo Charcoal: A Review

Abstract: Abstract. Bamboo charcoal was produced by pyrolysis or carbonization process with extraordinary properties such as high conductivity, large surface area and adsorption property. These properties can be improved by activation process that can be done thermally or chemically. In this paper, carbonization and activation process of bamboo, its structural and adsorption properties will be presented. Herein, the adsorption properties of bamboo charcoal that has fully utilized in solar cell as the electrode, adsorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Bamboo charcoal has been utilized in ample ways since 1486 AD because of its exceptional qualities [42,43]. By heating bamboo stems in an argon environment, [44] investigated and published a simple and customizable method for producing fluorescent carbon nanostructures.…”
Section: Bamboo-derived Charcoalmentioning
confidence: 99%
“…Bamboo charcoal has been utilized in ample ways since 1486 AD because of its exceptional qualities [42,43]. By heating bamboo stems in an argon environment, [44] investigated and published a simple and customizable method for producing fluorescent carbon nanostructures.…”
Section: Bamboo-derived Charcoalmentioning
confidence: 99%
“…In the MFC design, electrodes are desired to have the following characteristics: (i) high electrical conductivity and low resistance; (ii) high mechanical strength; (iii) strong biocompatibility, (iv) high chemical stability and corrosion resistance, (v) large surface area, (vi) low cost, and vii) environmental friendliness [1]. Bamboo charcoal meets most of the aforementioned characteristics [66,67,76,[79][80][81][82][83][84][85][86][87][88]. Figure 2 shows SEM images of the external surface and cross-section of the BC anode.…”
Section: Bamboo Charcoal Anodementioning
confidence: 99%
“…Bamboo is one of the potential feedstocks to substitute wood for charcoal production that can be produced via a pyrolysis process at high temperatures (800-1200•C) [6][7]. It is a renewable energy resource, cost-effective and ecofriendly product that can be an alternative to fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…It is also having an excellent adsorbent capacity that can be used to remove harmful gases, absorbs the unpleasant smell and being in water purification and wastewater treatment system [4]. Isa et al [3,6] also reported that bamboo charcoal has an enormous surface area to mass ratio with a microporous structure which has great absorption properties that can hold (adsorb) a wide range of materials, chemicals, minerals, radio waves, humidity, odours and harmful substances. Bamboo charcoal surface area (300 m 2 /g) is ten times greater than wood charcoal (30 m 2 /g) and larger than multi-walled carbon nanotubes (200 m 2 /g) [3].…”
Section: Introductionmentioning
confidence: 99%